The Effects of Gender and Maturation on Moral Reasoning Orientation, Care and Justice in Adulthood - Judy Lea Lavell (Adult Education Research Conference, 2002)
Using a causal comparative cross sectional approach with 380 subjects Ranging from 23 to 85 years of age, relationships between gender, maturation and moral reasoning orientation were explored. The two major findings were that older adults differed from younger adults in their classifications of moral orientation and gender played less of a role in moral reasoning than previously hypothesized.